UAS-SfM as a cost-effective tool for coastal monitoring and management - Lazogiannis, Κ.; Vassilakis, Emm.; Poulos, S.; Kotsopoulos, S.; Alexopoulos, J.D.; Alamanis, N.; Papageorgiou, G. (1st International Scientific Conference on Design and Management of Port Coastal and Offshore Works, 2019)
Coastal zone monitoring of river deltas is essential in order to understand their evolution and incorporate sustainable coastal management practices. Frequent data collection is essential but often surveys can be costly and time-consuming. This often leads to increase the time lag between successive monitoring campaigns to reduce survey costs, with the consequence of fragmenting the data available for coastal zone management. In this study we present the ability of off-the-shelf Unmanned Aerial Systems (UAS) coupled with Structure-from-Motion (SfM) photogrammetry to map and measure coastal features (e.g. shorelines).